Biorremediação em ambiente aquático com sistema em fluxo com a utilização de biofilme - Miyasato, Ana Carolina de Oliveira (Universidade Federal de São Carlos, 2023)
Currently, bioremediation has been widely used within the area of biotechnology along with the use of biofilms as bioremediators. Bacterial biofilms have an important bioremediation property in contaminated environments and/or with a high concentration of nutrients. This research aimed to carry out bioremediation in the lagoon of the Federal University of São Carlos, in Araras, a place that may contain concentrations of toxicity, coming from pesticides from surrounding plantations, heavy metals and/or fertilizers, with the objective of this research being to produce bacterial biofilms. and evaluate their effectiveness in treatment using two microorganisms: AL (acronym derived from the orange-yellow color, as it has no identification) which has a yellow color around the orange middle with a gelatinous appearance and BN (acronym derived from the neutral white color, as it does not have identification) which has a “finer” white appearance with a more transparent surrounding. The microorganisms were cultivated on two types of surfaces, on sugarcane bagasse (natural) and polyurethane foam (synthetic). Both substrates were subsequently used as immobilizing matrices as bioremediators in a flow system based on a continuous stirred tank reactor (CSTR). After the bioremediation tests, toxicity tests were carried out using Allium cepa roots in contact with solutions resulting from bioremediation, untreated raw water and control (distilled water) totaling six bulbs, one for each solution, using growth as a parameter ( uncontaminated solution) or stagnation of root growth (contaminated solution). Of the six tests with Allium cepa, two resulted in total growth stagnation, one of them being the raw untreated water solution from the lake, leading to the conclusion that the test aquatic environment has some type of toxicity. And in relation to the amount of biofilm adhered to each type of substrate, BN and AL microorganisms presented the same amounts of biofilm adhered to each type of substrate, with the polyurethane substrate proving to be more efficient than sugarcane bagasse. -sugar in approximately 100% of adhered solids, probably due to the properties of the lignin contained in sugarcane bagasse. This study proved to be important in relation to discoveries in the area of bioremediation and could contribute to future studies in the areas of microbiology, ecotoxicology and bioremediation; the possibility of using a natural substrate as a material for biofilm immobilization, cell immobilization and use in fermentation processes.
Bioremediation in an aquatic environment with a flow system using biofilm
Keywords: Imobilização; Allium cepa; Inibidores; Lignina; Immobilization; Growth-inhibitor; Lignin; CIENCIAS BIOLOGICAS::MICROBIOLOGIA